In-hospital thromboembolic complications after frozen elephant trunk aortic arch repair - Ibrahim, Marina; Chung, Jennifer C-Y; Ascaso, Maria; Hage, Fadi; Chu, Michael W A; Boodhwani, Munir; Sheikh, Azmat A; Leroux, Emilie; Ouzounian, Maral; Peterson, Mark D (The Journal of thoracic and cardiovascular surgery, 2024)
This study evaluated the frequency and clinical impact of thromboembolic complications after frozen elephant trunk aortic arch repair using the Thoraflex device (Terumo Aortic). A total of 128 consecutive patients (mean age 67.9 ± 13.7 years, 31.0% female) underwent frozen elephant trunk aortic arch repair using the Thoraflex device between September 2014 and May 2021 in 4 Canadian centers. Patient baseline characteristics, intraoperative details, and frozen elephant trunk thromboembolic complications were collected retrospectively and analyzed. Fifteen patients (11.7%) had thrombus visualized within the frozen elephant trunk stent graft on imaging (n = 8; 53.3%) or had a thromboembolic event (n = 9; 60.0%) before hospital discharge. Sites of embolism were mesenteric (n = 8; 88.9%), renal (n = 4; 44.4%), and iliofemoral (n = 1; 11.1%). Patients who experienced thromboembolic complications were more likely to have a history of autoimmune disease (n = 3; 20.0% vs n = 2; 1.8%; P = .01) and implantation of a longer frozen elephant trunk stent graft (150 mm vs 100 mm) (n = 13; 86.7% vs n = 45; 39.8%; P < .001). All patients with thromboembolic complications received therapeutic anticoagulation, and a smaller proportion required an open surgical (n = 5; 33.3%) or an endovascular (n = 2; 13.3%) intervention. Radiographic resolution of thromboembolic complications was observed in 86.7% of patients (n = 13). In-hospital mortality occurred in 1 patient, stroke occurred in 1 patient, and transient spinal cord injury occurred in 1 patient. Thromboembolic complications occur more often than previously recognized after frozen elephant trunk aortic arch repair using the Thoraflex device and are associated with increased rates of surgical and endovascular reintervention. Prevention and management of these complications require further study.